New Leadership and the Rise of Spectacularisation on TikTok: Electoral Strategies in Spain and their Impact on Citizens - Plazas-Olmedo, Maite; López-Rabadán, Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
TikTok is becoming a key political platform at the European level, especially during election campaigns. This study analyzes the specific Spanish case, specifically the leadership development of twelve mayoral candidates during the 2023 May 28th campaign, examining 268 videos from seven different municipalities and parties. Through a content analysis based on the 5W model, personalization, attributes, formal resources, and engagement are assessed. The results show a constant focus on citizens, highlighting professional qualities in leaders, and highlighting that more posts do not guarantee greater impact. Furthermore, six leadership typologies are identified based on regularity of use, professionalism, and narrative.